Behavioral evidence of saccharide mixture as a potent feeding effector for the purple mud crab Scylla tranquebarica - Liew, Kit Shing; Seow, Bel En; Rossita Shapawi; Liew, Hon Jung; Karsoon Tan; Kianann Tan; Reiji Masuda; Lim, Leong Seng (Springer Nature, 2024)
The present study evaluated the potential of a saccharide mixture (galactose, glucose, fructose, and sucrose in a 2:1:1:1 ratio) as a chemoattractant (attraction) or/and feeding stimulant (ingestion) for the purple mud crab Scylla tranquebarica. In Experiment I, the S. tranquebarica appetitive response toward the 3%, 5%, or 7% (w/v) saccharide mixture solutions was examined and evaluated by a scoring method. The 5% and 7% treatments yielded the highest mean score (2.05 out of 3.00), with 20% of the S. tranquebarica exhibiting the highest response order (probing movement) in the latter treatment. In Experiment II, the S. tranquebarica feeding response toward the pelleted feeds containing the saccharide mixture at 3%, 5%, or 7% (SAC3, SAC5, or SAC7) was examined and evaluated using a scoring method. No significant difference (P > 0.05) was found among the mean scores of SAC3, SAC5, and SAC7. However, the mean score of the SAC7 diet was significantly higher (P < 0.05) than that of the control feed (without saccharide mixture inclusion), with 25% of the S. tranquebarica ingesting the feed. These findings highlight the potency of the saccharide mixture as a feeding effector for S. tranquebarica.